Фестивальний рух у місті Києві за роки незалежності - Бортник, Сергій Юрійович; Поліщук, Ірина Григорівна; Сидорук, Юлія Олександрівна (Київський національний університет імені Тараса Шевченка, 2016)
Purpose of the article is a historical and retrospective analysis of festival’s movement in Kyiv as one of the most important components of the cultural and artistic life of the capital of Ukraine in the context of "urban geography." Method. The research consistes in synthesis and analysis of collected large amount of material. It has been used tabular and cartographic methods. For our research was taken the period from 1991 and 2016. Іn the scientific literature it has been defined as a period of "festival boom". Results. The article analyzes structure of genres, spatial and temporal features and geography of the festival movement in Kyiv. Based on this developed appropriate classifications of festivals and creation of a comprehensive map of geography largest and most significant festivals of the city. It was revealed the basic trends of festival’s spaces in Kyiv during the years of independence of Ukraine and was analyzed positive and negative aspects of modern festivals. Scientific novelty. For the first time were analyzed festival’s movement in Kiev during the years of independence. Were collected extensive factual material created in accordance maps. The practical significance of the research was defined by its practical importance for the development of festival’s tourism, is a resource for improving global image of the capital and whole Ukraine, and also it is a source that rise the economic potential of the city. It creates the basis for significant growth and diversification of employment, increases flow of both native and foreign tourists, increases wealth and cultural level of the population.

Метою статті є історико-ретроспективний аналіз фестивального руху у місті Києві як одного із найважливіших складових культурно-мистецького життя столиці в контексті «міської географії». Методика. Дослідження полягали в синтезі та аналізі зібраного авторами великого фактичного матеріалу. При цьому застосовувались табличний та картографічний методи. Для дослідження був узятий період з 1991 по 2016 рр., який у науковій літературі визначається як період «фестивального буму». Результати. У статті проаналізовано жанрову стурктуру, просторово-часові особливості організації та географію фестивального руху в місті Києві. На основі цього розроблено відповідні класифікації фестивалів та створенна комплексна карта географії найбільших й найзначиміших фестивалів міста. Висвітлено основні тенденції розвитку фестивального простору міста Києва за роки незалежності, проаналізовано позитивні та негативні риси сучасних фестивалів. Наукова новизна. Вперше проаналізовано фестивальний рух у місті Києві за роки незалежності. Зібрано великий фактичний матеріал, створено відповідні карти. Практична значимість дослідження визначається його важливістю для практичного розвитку фестивальний туризм, що є ресурсом підвищення світового іміджу столиці, джерелом підйому економічного потенціалу міста. Проведення фестивалів у місті створює основу для суттєвого зростання та урізноманітнення зайнятості, матеріального добробуту та культурного рівня населення.
Festival Movement During the Years of Independency in Kiev
Keywords: фестиваль; фестивальний рух; географія фестивалів; festival; festival’s movement; geography of festivals